PENGEMBANGAN USAHA NUGGET BERBAHAN DASAR IKAN LOUHAN SEBAGAI UPAYA PENINGKATAN EKONOMU MASYARAKAT BERBASIS POTENSI LOKAL DI DESA SILALAHI II, KECAMATAN SILAHISABUNGAN, KABUPATEN DAIRI, KULIAH PRAKTIK PENGABDIAN KEPADA MASYARAKAT - Naik Mauli Harefa; Lastri; Wilson Wahyudi Raja Sihombing (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This community service activity aimed to develop a local resource-based business through the utilization of louhan fish as the main ingredient for nugget production in Silalahi II Village, Silahisabungan District, Dairi Regency. The activity was motivated by the underutilization of louhan fish as a product with added value and greater economic potential. The program was implemented through socialization, training, hands-on practice, and mentoring activities involving community members, particularly housewives and village youth. A participatory approach was employed to encourage active community involvement throughout all stages of the program. The results of the activity indicated an improvement in participants’ knowledge and skills in processing louhan fish into value-added nugget products. Furthermore, the program provided insights into local resource-based business opportunities and highlighted the importance of product innovation in enhancing the economic value of fishery products. The resulting louhan fish nuggets offer an alternative form of fishery product diversification with the potential to be developed as a household-scale business. Therefore, this community service activity is expected to promote community empowerment, strengthen the utilization of local resources, and support sustainable community economic development.